Measurement of the tensor analysing power of the negative pion photoproduction on the deuteron; Fundamental problems of nuclear physics, atomic power engineering and nuclear technologies (Nucleus 2010) - Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Loginov A. Yu.; Nikolenko D. M.; Osipov A.V.; Rachek I. A.; Sidorov A. A.; Stibunov V. N. Victor Nikolaevich; Toporkov D. K.; Shestakov Yu.V.; Zevakov S. A. (2010, 2010)
В фонде НТБ ТПУ отсутствует